2018
DOI: 10.1002/jat.3725
|View full text |Cite
|
Sign up to set email alerts
|

Individual and combined toxicity of T‐2 toxin and deoxynivalenol on human C‐28/I2 and rat primary chondrocytes

Abstract: Deoxynivalenol (DON) and T‐2 toxin are prevalent mycotoxin contaminants in the food and feed stuffs worldwide, with non‐negligible co‐contamination and co‐exposure conditions. Meanwhile, they are considerable risk factors for Kashin‐Beck disease, a chronic endemic osteochondropathy. The aim of this study was to investigate the individual and combined cytotoxicity of DON and T‐2 toxin on proliferating human C‐28/I2 and newborn rat primary costal chondrocytes by MTT assay. Four molar concentration combination ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
(66 reference statements)
0
13
0
Order By: Relevance
“…The authors explained this interaction by the competition between the mycotoxins for the same target/receptor site [14,19]. Lin et al [92] suggested that the effect of DON and T-2 is additive/synergistic at middle and high concentrations but antagonistic at low concentrations in rat chondrocytes and C-28/I2 cells. Additionally, synergic effect was also detected when the individual levels were at nearly the same ratio and antagonistic effect when the concentration of DON was much higher (100-1000×) than T-2 [92].…”
Section: Acute Toxicity Of Mycotoxins In Binary Mixturesmentioning
confidence: 99%
“…The authors explained this interaction by the competition between the mycotoxins for the same target/receptor site [14,19]. Lin et al [92] suggested that the effect of DON and T-2 is additive/synergistic at middle and high concentrations but antagonistic at low concentrations in rat chondrocytes and C-28/I2 cells. Additionally, synergic effect was also detected when the individual levels were at nearly the same ratio and antagonistic effect when the concentration of DON was much higher (100-1000×) than T-2 [92].…”
Section: Acute Toxicity Of Mycotoxins In Binary Mixturesmentioning
confidence: 99%
“…One urine sample contained only one mycotoxin, while 20 combinations of two or up to seven mycotoxin urinary biomarkers were observed; more than 70% of the urines contained ve or more different mycotoxins. Complex mixture toxicology remains poorly examined though several groups have recently examined combined effects in vitro [47,48,49,50,51,52,53,54,55,56,57,44,45], with animal studies being more limited [58,59]. These studies remain hard to interpret for public health decisions, but some suggest more than additive effects, thus the mixtures reported here and elsewhere highlight signi cant knowledge gaps.…”
Section: Discussionmentioning
confidence: 95%
“…Analogously to previous research (Y. Lei et al, ), DON exposure induced cell apoptosis, concomitant with increased activities of caspase‐3 and caspase‐9. Accordingly, excessive chondrocyte apoptosis is extensively studied as a contributing factor to the pathology of KBD (Lin et al, ; H. J. Yang et al, ; L. Yang, ). Therefore, these findings highlight the adverse effects of DON on chondrocyte that may be involved in the development of KBD.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive chondrocyte apoptosis is accepted as a primary pathological contributor to KBD. Recently, it was demonstrated that exposure to DON has been reported to induce cell apoptosis, oxidative stress, and cell cycle arrest in human C28/12 chondrocyte line (Y. Lei et al, ; Lin et al, ). However, the effects and underlying mechanism of DON in the development of KBD remain unclear.…”
Section: Introductionmentioning
confidence: 99%